Notary's Authority to Make Deeds of Name Loan Agreement (Nominee) Related to Sale And Purchase a Land Involving Foreigners - Irawan Aprian; Gatot Dwi Hendro Wibowo; Kurniawan (MultiTech Publisher, 2024)
This research aims to analyze whether the authority to make deeds of a Notary applies to all forms of agreement and what is the Notary's responsibility for making Deeds of loan agreements (nominees) related to buying and selling land involving foreigners. This legal research method uses normative legal research. The approach used is a statutory approach and a conceptual approach. From this research the author found, firstly, that there is disharmony between article 15 paragraph (1) a of Law number 2 of 2014 concerning amendments to Law number 30 of 2004 concerning the Position of Notaries hereinafter abbreviated as UUJN and Law number 5 of 1960 concerning the Basic Regulations on Agrarian Principles, hereinafter abbreviated to UUPA. Where in article 15 paragraph (1) a UUJN which states that Notaries have the authority to make authentic deeds regarding all deeds, agreements and provisions required by statutory regulations and/or which are desired by interested parties to be stated in authentic deeds, this is often a loophole in a acts of legal smuggling carried out by foreigners and Indonesian citizens and often involving notaries in a loan agreement (nominee) related to the sale and purchase of land involving foreigners, which is contrary to UUPA article 21 which states that only Indonesian citizens can have property rights. Due to this conflict of norms, the authority to make deeds of a notary does not apply to all forms of agreements. Secondly, if the notary is proven to have committed an act of legal smuggling, the notary must be responsible for his actions both civilly, administratively and criminally.